Endlings : fables for the anthropocene. - PYNE, LYDIA (UNIV OF MINNESOTA PRESS, 2022)
Amid the historical decimation of species around the globe, a new way into the language of loss An endling is the last known individual of a species; when that individual dies, the species becomes extinct. These "last individuals" are poignant characters in the stories that humans tell themselves about today's Anthropocene. In this evocative work, Lydia Pyne explores how discussion about endlings--how we tell their histories--draws on deep traditions of storytelling across a variety of narrative types that go well beyond the science of these species' biology or their evolutionary history. Endlings provides a useful and thoughtful discussion of species concepts: how species start and how (and why) they end, what it means to be a "charismatic" species, the effects of rewilding, and what makes species extinction different in this era. From Benjamin the thylacine to Celia the ibex to Lonesome George the Galápagos tortoise, endlings, Pyne shows, have the power to shape how we think about grief, mourning, and loss amid the world's sixth mass extinction.